Cap-assisted forward-viewing endoscopy to visualize the ampulla of Vater and the duodenum in patients with familial adenomatous polyposis - Kallenberg, Frank G. J.; Bastiaansen, Barbara A. J.; Dekker, Evelien (Endoscopy, 2017)
Background and study aims Guidelines recommend surveillance endoscopy with both forward- and side-viewing endoscopes to identify duodenal and ampullary adenomas in patients with familial adenomatous polyposis (FAP). We hypothesized that both the duodenum and the ampulla of Vater can be completely visualized during cap-assisted forward-viewing endoscopy. Patients and methods A total of 40 patients with FAP underwent forward-viewing endoscopy with a short cap attached to the tip of the gastroscope, with the aim of visualizing both the duodenum and the ampulla of Vater. If unsuccessful, the procedure was followed by a side-viewing endoscopy. Adverse events were reported.Results The duodenum, including the ampulla of Vater, was completely visualized using the cap in 38/40 patients (95.0 %). The ampulla could not be visualized using the cap in two patients, both of whom underwent additional side-viewing endoscopy, which was successful. No adverse events occurred.Conclusions This study showed that cap-assisted endoscopy can be used effectively and safely to visualize both the duodenum and the ampulla of Vater in patients with FAP. This practice might reduce burden, time, and costs of an additional side-viewing endoscopy.